Pilihan Hidup Tokoh Utama Zarah Amala dalam Novel "Supernova Episode: Partikel" Karya Dee Lestari: Kajian Feminisme Liberal - Wahid Tawaqal; Mursalim Mursalim; Irma Surayya Hanum (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2020)
This research raises the topic of liberal feminism Zarah Amala, the main character in the Supernova Episode: Partikel by Dee Lestari. The purpose of this research is to describe the liberal feminist attitude of the main character and at the same time describe the impact of the life choice of the main character on the main additional character. This research is a type of library research. The discussion of liberal feminism studies uses the theory developed by Wolf (1997), namely the Feminism of Power and the theory of figures and characterizations. Zarah practices liberal feminism in the form of Power Feminism, among others: (1) observing power against women, (2) firmness in choice, (3) desire that women are not destitute, (4) tolerant, (5) women's competition, and (6) ) have strong confidence. The figures affected by the liberal feminism idea adopted by Zarah were a group of main additional figures: (1) Firas: Zarah gives loyalty so that her father does not feel alone; (2) Aisyah: Zarah made Aisyah feel depressed because of the quarrel they were maintaining; (3) Abah Hamid: Zarah is no longer considered a grandchild because of her very different views; (4) Hara: Zarah has a stake in the character of her mature and stoic sister; (5) Ibu Inga: Zarah becomes a foster mother of an orangutan. (6) Paul: Zarah makes Paul fall in love; (7) Simon: Zarah makes Simon busier than usual; (8) Koso: Zarah becomes a loyal friend; and (9) Storm: Zarah gives her virginity to Storm.